Pragmatics of Tense and Time in News : From canonical headlines to online news texts. - Chovanec, Jan (Pragmatics & beyond ;, 2014)
This book provides the first comprehensive account of temporal deixis in English printed and online news texts. Linking the characteristic usage of tenses with the projection of deictic centres, it notes how conventional tenses, particularly in headlines, are affected by heteroglossia arising from various accessed voices. The resulting tense shifts are interpreted pragmatically as a conventional reader-oriented strategy that creates the impression of temporal co-presence. It is argued that since different tense choices systematically correlate with the three main textual segments of news texts.